Elevated atmospheric CO2 modifies responses to water‐stress and flowering of Mediterranean desert truffle mycorrhizal shrubs. Issue 4 (16th September 2020) - Marqués‐Gálvez, José Eduardo; Navarro‐Ródenas, Alfonso; Peguero‐Pina, José Javier; Arenas, Francisco; Guarnizo, Angel Luigi; Gil‐Pelegrín, Eustaquio; Morte, Asunción
Abstract : Predicted increases in atmospheric concentration of carbon dioxide (CO2 ) coupled with increased temperatures and drought are expected to strongly influence the development of most of the plant species in the world, especially in areas with high risk of desertification like the Mediterranean basin. Helianthemum almeriense is an ecologically important Mediterranean shrub with an added interest because it serves as the host for the Terfezia claveryi mycorrhizal fungus, which is a desert truffle with increasingly commercial interest. Although both plant and fungi are known to be well adapted to dry conditions, it is still uncertain how the increase in atmospheric CO2 will influence them. In this article we have addressed the physiological responses of H. almeriense × T. claveryi mycorrhizal plants to increases in atmospheric CO2 coupled with drought and high vapor pressure deficit. This work reports one of the few estimations of mesophyll conductance in a drought deciduous Mediterranean shrub and evaluates its role in photosynthesis limitation. High atmospheric CO2 concentrations help desert truffle mycorrhizal plants to cope with the adverse effects of progressive drought during Mediterranean springs by improving carbon net assimilation, intrinsic water use efficiency and dispersal of the species through increased flowering events.